1997
DOI: 10.1093/ajcn/65.2.439
|View full text |Cite
|
Sign up to set email alerts
|

Validation of single daytime samples of human milk to estimate the 24-h concentration of lipids in urban Guatemalan mothers

Abstract: The large within- and between-sample variability in breast milk lipid content greatly complicates the collection of representative samples in field studies. The main purpose of this study was to validate the ability of individual daytime samples to predict the 24-h lipid concentration of breast milk. We also studied maternal, child, and other factors (time of day and interval between feeds) associated with the within- and between-mother variability in milk lipid content. Fifty-two primiparous urban Guatemalan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
51
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 22 publications
10
51
0
Order By: Relevance
“…By contrast, Prentice et al (1981a) reported higher levels of milk fat in the morning compared with the afternoon in rural Africa, possibly attributed to a greater degree of night feeding in this non-Western population. Standardizing milk collection to a particular time of day, preferably in the morning, is preferred for milk collection protocols (Garza and Butte, 1986;Ruel et al, 1997).…”
Section: Sources Of Variation In Human Milkmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, Prentice et al (1981a) reported higher levels of milk fat in the morning compared with the afternoon in rural Africa, possibly attributed to a greater degree of night feeding in this non-Western population. Standardizing milk collection to a particular time of day, preferably in the morning, is preferred for milk collection protocols (Garza and Butte, 1986;Ruel et al, 1997).…”
Section: Sources Of Variation In Human Milkmentioning
confidence: 99%
“…In particular, the changes in fat and fat-soluble components of milk can be problematic for researchers attempting to collect a representative milk sample (Garza and Butte, 1986). Herein, we review several sampling methods that may be of interest to researchers (Butte et al, 1983;Neville, 1995;Neville et al, 1984Neville et al, , 2002Picciano, 1984;Prentice et al, 1981a;Ruel et al, 1997) but should note that this list is primarily targeted toward human biologists and will not contain all methodologies currently available to clinicians. Ultimately, the sampling protocol should be the ''best fit'' for the milk constituent of interest while also considering possible limitations from the population or the field conditions (Neville, 1995).…”
Section: Milk Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all the nutrients in human milk, lipids show the greatest variability. Milk fat composition may be influenced by maternal diet (Lönnerdal, 1986;Ruel et al, 1997;Francois et al, 1998;Jensen, 1999;Pugo-Gunsam et al, 1999;Koletzko et al, 2001), but significant variations have also been found in the same woman between feeds (Boersma et al, 1991;Jensen, 1999), within a feed (Ruel et al, 1997;Jensen, 1999), and between breasts (Hytten, 1954;Brown et al, 1982;Neville et al, 1984;Jensen, 1999). Significant differences in triacylglycerol (TAG) content have been found between samples taken before and after nursing (Hromadová et al, 1991) and among samples from different lengths of lactation (Harzer et al, 1983;Lyapkov & Kiseleva, 1992b;Martin et al, 1993;Morera et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Fat is the macronutrient in milk that varies most in concentration and has been shown to be higher in well-nourished mothers than in their poorly nourished counterparts (5) . Fat concentration is higher in mature milk than in colostrum, and somewhat higher in breast milk of mothers from affluent compared with poor societies (6) .…”
Section: Breast Milk Fat and Retinolmentioning
confidence: 99%